2008
DOI: 10.1002/jbm.a.32187
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of valvular interstitial cell calcification by components of the extracellular matrix

Abstract: The composition of the extracellular matrix (ECM) is believed to play a role in heart valve disease, and is highly relevant to the design of heart valve tissue engineering scaffolds, yet the interaction of valvular interstitial cells (VICs) with the ECM environment has not been well characterized. Thus, the transformation of VICs to an osteoblast-like phenotype was quantified in VICs cultured on different types of ECM coatings. The results show that the number and size of calcific nodules formed in VIC culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
100
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(108 citation statements)
references
References 36 publications
7
100
1
Order By: Relevance
“…In single layers, SMαA expression was much lower by 4 days, indicating a VIC transition from an activated state to a more quiescent state that is often found in healthy valves in vivo. Reduction in VIC SMαA expression likely occurred due to culture on collagen-I substrates, as shown by collagen's ability to reduce VIC calcification found in earlier studies with collagen [11].…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…In single layers, SMαA expression was much lower by 4 days, indicating a VIC transition from an activated state to a more quiescent state that is often found in healthy valves in vivo. Reduction in VIC SMαA expression likely occurred due to culture on collagen-I substrates, as shown by collagen's ability to reduce VIC calcification found in earlier studies with collagen [11].…”
Section: Discussionmentioning
confidence: 73%
“…These studies have shown that VIC activation and calcification potential are measurably influenced by the substrate stiffness of the culture ECM or biomaterial [9]. Stiffer substrates such as polystyrene promote VIC calcification whereas collagen, hyaluronan, and fibronectin gels or surface coatings reduce calcification [11][12][13]. Production of calcific nodules by VICs is a complicated process, however, involving multiple cell signaling pathways that are influenced by inflammatory factors, growth factors such as TGF-β, substrate stiffness, biological activity of the substrate, and oxygen and nutrient availability [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, myofibroblast differentiation from VICs and calcification in vitro have been shown to be dependent on ECM composition [19].…”
Section: The Aortic Valve Leaflets Are Layered Structuresmentioning
confidence: 99%
“…In vitro studies were unable to induce calcification in VICs cultured on collagen proteins in standard media. It is believed that collagen actively inhibits VIC calcification [19]. Other studies have shown that scaffold collagen content also affects VIC proliferation.…”
Section: Collagen Comprises a Significant Portion Of The Aortic Valvementioning
confidence: 99%
See 1 more Smart Citation